(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2015)
The latest national and international researches emphasize childhood as a key factor in the course of life of the individual. In recent years, research on young children’s early brain (head) and emotional development (heart) have underscored its importance for later development. Integrating this ‘Brain-Based, Heart-Felt’ research into classroom practice, however, will require meaningful dialogue between educators and brain scientists to inform both research and ECE institutions. Our group aims to bring educators and scientists together through the development of joint research projects to improve the understanding of how children learn and develop. Linking brain and EQ research to ECE is extremely valuable to our understanding of children development and learning. The research will provide educational sciences with lots of new information and data whereas it will also modify and complement the content of nursery school teacher and early childhood educator trainings as well as the innovation of early childhood educational and research facilities.